Analisis Konsep Penilaian Autentik dalam Evaluasi Pembelajaran di Sekolah - Hani Yatul (PGRI University Yogyakarta, 2025)
In the educational arena, the learning process consists of three main identifiable elements: educational objectives (teaching), the learning process, and learning outcomes. The core of educational objectives is the desired behavioral change in students. Therefore, evaluation should assess the extent of student behavioral change after they have undergone the learning process. Knowing whether educational objectives have been achieved allows us to take actions to improve education, including changes in learning strategies and student quality, as well as achieving infrastructure. Recommendations are provided to support the creation of an effective, efficient, and beneficial learning process. The Independent Curriculum was created to address the rapid changes of the times, emphasizing student-centered learning and authentic assessment. Authentic assessment aims to evaluate students' abilities through activities relevant to real-world situations, encompassing aspects of attitudes, knowledge, and skills. This research uses a literature review method with a descriptive qualitative approach to investigate the concepts, practices, and challenges encountered in implementing authentic assessment in the Independent Curriculum. Keywords: Assessment, Authentic Assessment, Evaluation